Traumatic perforation of the esophagus in the cervical thoracic passage - Liard, Washington; Kalechsztajn, Jaime; Gilardoni, Federico (Cirugía del Uruguay, 1972)
We present a case of traumatic perforation of the esophagus at the level of the cervico-thoracic passage treated early by cervical esophagotomy, drainage and gastrostomy. Successful evolution.